TIME-SAVING DESIGN AIDS FOR ONE-WAY HOLLOW SANDCRETE BLOCK SLAB (FULafia Journal of Science and Technology, 2018)
Although efficient computer programs are available for analysis and design of most structural systems, design aids are very important in engineering designs. This research study presents a time-saving design aids for oneway hollow sandcrete block slab. The slabs are designed to conform to the specifications of BS 8110, and are intended in design offices for preliminary designs and for checking computer results output